Cultural strivers: trajectories of upward mobility in the popular classes (Educação e Pesquisa, 2022)
This article aims to discuss trajectories of upward mobility among Brazilian popular classes through the acquisition of educational capital and access to higher education in the last decades. The investigation is based on Bourdieu’s dispositionalist approach, focused on objective and subjective conditions that allowed some members of the popular classes to break through class boundaries, since social mobility took place through access to higher education. This research was qualitative, involving in-depth interviews with members of this class fraction residing in the metropolitan area of Recife (Pernambuco) between 2015 and 2016. In this work, people who participated are called cultural strivers, given their upward mobility through the incorporation of an amount of cultural capital. The research sought to reconstruct these members’ trajectories and the main dispositions and values constitutive of their class ethos, responsible for their upward mobility process via schooling. The analysis identified a set of dispositions incorporated in the course of these individuals’ trajectories which favored the acquisition of educational capital and other forms of cultural capital, propelling them to the top of that class fraction. On the other hand, it is possible to observe the tensions and conflicts associated with their attempts to “come out on top”, as well as adjustments of the expectations (generated by acquiring a college degree) to reality, given the limited opportunities found by graduates.